2020
DOI: 10.3390/ijerph17103545
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sedentary Behavior and Depression among College Students Majoring in Design

Abstract: Background: This study aimed to specify the prevalence of sedentary behavior and depression and investigate the relationship between sedentary behavior and depression among college students majoring in design. Methods: A total of 480 undergraduate and postgraduate students majoring in design were randomly enrolled from a university in Nanjing for a questionnaire that included sociodemographic data, physical health, sedentary behavior and depression. Results: Participants reported that they spent 14.93 (SD = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
3
22
1
Order By: Relevance
“…Moreover, our study showed that SB is a risk factor independent of VPA for depression among sports university students, which is consistent with most previous research taking depression as a health outcome [ 7 , 17 , 18 ]. Participating in PA at considerably higher than recommended levels may be able to decrease the mortality risk associated with SB [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, our study showed that SB is a risk factor independent of VPA for depression among sports university students, which is consistent with most previous research taking depression as a health outcome [ 7 , 17 , 18 ]. Participating in PA at considerably higher than recommended levels may be able to decrease the mortality risk associated with SB [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Third, the variables in our research were self-reported, which renders them vulnerable to subjectivity. The use of SB questionnaires is a developing field [ 18 ]. Generally, self-reported SB is lower than the results measured by an accelerator [ 5 ], but it is more applicable when investigating domain-specific SB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings agree with others where, among undergraduate university students, hierarchical regression showed that strenuous PA participation predicted the number of health complaints [ 73 ]; and in the UK, students with higher PA reported better outcomes for mental and personal well-being [ 25 ]. Among university students in China, after adjusting for sociodemographic characteristics, physical health and physical activity, binary logistic regression analysis showed that the total sedentary time were significantly associated with depression [ 74 ]. Similarly, among school-aged adolescents, PA level was independently associated with psychological HCs, where the average psychological HCs score increased when moving from the high to low PA categories [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous studies, this method takes advantage of the online map service, the reliability of which is bolstered by the feedback of numerous users. This helps researchers to reduce their reliance on traditionally official data, hence saving time in data acquisition and field investigation [46].…”
Section: Discussionmentioning
confidence: 99%